Forgotten Castle Landscapes: Connecting Monuments and Landscapes through Heritage and Research. (3rd July 2019) - Pluskowski, Aleks; Banerjea, Rowena; García-Contreras, Guillermo
ABSTRACT: This paper introduces the theme of a special issue exploring the connections between castles (broadly defined as medieval fortified sites) and their landscapes, from archaeological and heritage perspectives. It includes a brief case study of how some of the castles in Occitanie, southern France, have been connected with their landscapes in the construction of Le Pays Cathare within the context of promoting regional tourism. GRAPHICAL ABSTRACT: